Equity: Problems in the implementation of education policies and reforms in Malaysia - Nordin, A.B. (2011)
Democratization of education implied that all children of school age should have the right to be in schools and also have the right to be assisted to achieve as much as what their cohorts have achieved or what has been specified by the curriculum. This is in line with the United Nations Convention on the rights of the child (1989 & 1990). However, owing to variations in factors such as family economic and education backgrounds, ethnicity, school locations, school and teacher distributations, allocation of school funds, diversity in the implementations of specific reforms, the presence of physically and mentally handicapped students and parent- teacher association involvement in school activity; accessibility and achievement fell short of the expectation. Admittedly to overcome the negative impacts of all those factors is almost impossible, nevertheless, if democratization of education were to be meaningful and beneficial to the children concerned drastic steps need to be considered and undertaken to ameliorate the negative impacts of those factors. In examining the current forms of policy implementation and reforms discrepancies found run not only counter to the sacred doctrine of democratization of education but also work against the sacred goals of providing equal education opportunity for all children. A very good example which helps to illustrate this statement is the practice of segregation between low performed students and high performed students based on performance in year or grade-six assessment (UPSR) and Lower secondary school evaluation (PMR). Streaming according to performance, despite having its own advantages does not help in either accessibility or achievement and thereby antithetical to equity. Therefore the current practices in the implementation of the policy and reforms should be re-examined within the context of a reliable framework so that remedial and much more innovative considerations such as purposeful distributions of teachers, making additional fund available for needy schools, streaming according to the needs of children to be able to learn effectively and dispensing some allocation and organizational skills to educate parents to be actively involved in school activities can purposefully be undertaken.